Plate VIII: Invertebrate development - Haeckel, Ernst (Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, 1872)
Plate depicts the development of invertebrates, possibly sea anemones. Haeckel is known for his descriptive work on marine organisms including radiolarians, poriferans (sponges), and cnidarians (jellyfish, anemones and corals). This plate can be found in Ernst Haeckel's Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, or The History of Creation: Or the Development of the Earth and Its Inhabitants by the Action of Natural Causes.
Keywords: Evolution; Heredity; Invertebrates; Sea anemones; Cnidaria